1989
DOI: 10.1111/j.1699-0463.1989.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasms of the central nervous system in Norway

Abstract: The association between meningioma and a primary malignant neoplasm at another site was studied. The data from the population‐based Norwegian Cancer Registry were analysed according to whether the meningioma occurred before or after the malignant neoplasm. Male patients with meningioma showed a raised risk for developing a subsequent renal cancer. A significant association was found between meningioma and subsequent breast cancer in females 50–64 years old at time of meningioma diagnosis and between breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…When compared with studies from western countries, we observed a comparable frequency of nerve sheath tumors as well as of the neuroepithelial tumors in our series, whereas the incidence of meningioma was low (6.3%) as compared to that reported by western authors (16-46%). [10,11,[16][17][18] However, the latter was similar to report by studies from Japan [6] to China [7] (11-15%). This compares favorably with epidemiological studies that Asian populations have a relatively less incidence of spinal meningioma than western countries.…”
Section: Discussionsupporting
confidence: 83%
“…When compared with studies from western countries, we observed a comparable frequency of nerve sheath tumors as well as of the neuroepithelial tumors in our series, whereas the incidence of meningioma was low (6.3%) as compared to that reported by western authors (16-46%). [10,11,[16][17][18] However, the latter was similar to report by studies from Japan [6] to China [7] (11-15%). This compares favorably with epidemiological studies that Asian populations have a relatively less incidence of spinal meningioma than western countries.…”
Section: Discussionsupporting
confidence: 83%
“…English-language full text was not available for 26 records; hence, they were excluded. Finally, 53 studies were included for this systematic review: 27 case reports, 14 case series and 12 cancer registry studies . The case reports, case series, and cancer registry studies described a total of 2238 individual patients diagnosed with both pathologies, including patients with intracranial collision tumors.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the breast cancer studies, the heterogeneity test results were highly statistically significant (Cochran Q = 345.5; df = 10; P < .001), with an I 2 of 98%, indicating that the between-study heterogeneity was high. Therefore, a random-effects model was chosen for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliomas are the most prevalent subgroup of primary brain tumors, a heterogeneous group of uncommon brain cancers with a relatively high mortality. However, there is a rare type among these tumors that are considered to have a better prognosis compared to other subtypes, due to their sensitivity to chemotherapy, known as Oligodendrogliomas ( 1 - 10 ). Recently, a correlation has been found between the response of these tumors to chemotherapy with certain genetic anomalies, including loss of 1p and 19q ( 1 , 5 , 7 , 8 , 11 ).…”
Section: Introductionmentioning
confidence: 99%